I'm too fond of my fur! (New York : Scholastic, 2004)
Geronimo follows clues in a diary all the way to Mouse Everest in search of his old friend Professor von Volt who has mysteriously disappeared.
"English translation... by Edizioni Piemme S.p.A."--T.p. verso.
G2
Keywords: Mice -- Fiction; Animals -- Fiction; Journalists -- Fiction; Mountaineering -- Fiction; Adventure and adventurers -- Fiction; Humorous stories